Event-free survival at 12 months is a strong surrogate endpoint for stage 1 diffuse large B cell lymphoma: a report from Nation Wide Registry Thai Lymphoma Study Group. Issue 11 (18th September 2020) - Wudhikarn, Kitsada; Bunworasate, Udomsak; Julamanee, Jakrawadee; Lekhakula, Arnuparp; Ekwattanakit, Supachai; Khuhapinant, Archrob; Niparuck, Pimjai; Chuncharunee, Suporn; Numbenjapon, Tontanai; Prayongratana, Kannadit; Kanitsap, Nonglak; Wongkhantee, Somchai; et al.
Abstract: Event-free survival at 12 months (EFS12) is a surrogate endpoint for long-term outcomes in many histologic lymphoma subtypes. However, most reports have primarily investigated the implication of EFS12 in advanced-stage non-Hodgkin lymphoma (NHL). There are limited data regarding the significance of EFS12 in early-stage NHL. Herein, we evaluated the prognostic significance of EFS12 in patients with stage 1 diffuse large B-cell lymphoma (DLBCL). Out of 282 patients with stage 1 DLBCL who received intensive therapy, 227 (80.5%) achieved EFS12. The 4-year overall survival (OS) was 91.4% and 4.0% for patients who achieved and failed to achieve EFS12, respectively. Multivariable analyses demonstrated response to treatment and achievement of EFS12 as independent predictors for OS. In conclusion, our study demonstrated EFS12 as a powerful prognostic factor for stage 1 DLBCL. Further validation in more extensive prospective studies is warranted.